Can Brand Switching of Consumers of The Originote Skincare Products in Sidoarjo Be Influenced by Electronic Word Of Mouth (E-WOM), Variety Seeking, and Service Quality? - Wijayanti, Evi; Sari, Dewi Komala; Supardi (Al Tijarah, 2024)
This study aims to determine whether the Brand Switching of The Originote Skincare Product Consumers in Sidoarjo is Influenced by Electronic Word Of Mouth (E-WOM), Variety Seeking, and Service Quality? This study uses a descriptive quantitative method, in its own population are users of The Originote skincare products with a sample of 100. The sampling technique uses a purposive sampling technique with respondents being the people of Sidoarjo at least 17 years old. The data collection technique uses a questionnaire that will be distributed through social media, and the answers are measured using a Likert scale. This study uses PLS-SEM data analysis. The results of this study prove that Electronic Word Of Mouth influences Brand Switching of The Originote Skincare consumers, Variety Seeking influences Brand Switching of The Originote Skincare consumers, and Service Quality influences Brand Switching of The Originote Skincare consumers.